(untitled) (Research, Society and Development, 2022)
The experience took place in a pediatric unit of a university hospital in the extreme south of Brazil, during the teaching internship with students of the undergraduate nursing course during the Master’s, having an important impact on the experience and subsequent professional performance. In this work, the objective was to report the experience in nursing care for children and family members during hospitalization in a Pediatric Unit. The family members appreciate the availability of the team to meet their needs and when they receive information that enables them to care for the child, they feel satisfied. As a strategy to improve care, there is a need for greater openness and willingness of the nursing team professionals to provide explanations about the child’s therapeutic process, making more participants in decision-making about it. It was concluded that it is necessary for the professionals of the nursing team to support the child’s family in the hospital in order to humanize the Pediatrics Unit, qualifying assistance, listening in order to meet the individual demands of each being / family involved in the process. caution.